The Analysis of the Development of Lake Kerinci Tourism Objects on the Economic Impact of the Community in Sanggaran Agung Village, Danau Kerinci District - Fitriya, Sri (The Future of Education Journal, 2025)
Indonesia is a country that has natural beauty and cultural diversity, so it is necessary to improve the tourism sector. Tourism is a sector that plays an important role in efforts to increase regional income and the income of people who are tourism actors. This study aims to determine what strategies are taken by the Kerinci Regency government through the development and management of the Kerinci Lake tourist attraction which has an impact on improving the economy of the Sanggaran Agung village community located around the Kerinci Lake tourist attraction. The type of data used is primary data with data collection through interviews. Data is processed using the SWOT Analysis method. The results of the study indicate that important strategies that can be carried out in the development of the Kerinci Lake tourist attraction are to provide facilities and organize and repair the facilities and infrastructure of tourist attractions, increase tourist attractions and interesting photo spots at tourist attractions, and develop UMKM and business actors who produce and provide souvenirs and culinary specialties of Kerinci and make the community a professional manager of tourist accommodation services by maintaining strengths and optimizing opportunities while improving weaknesses and anticipating existing threats. The method used to increase community income through the development and management of the Kerinci Lake tourist attraction is to increase the number of tourist visits, adequate governance/infrastructure and community services and a well-maintained environment.